Małżeństwa mieszane wedle koncepcji Kościoła katolickiego, Kościoła prawosławnego oraz Kościoła ewangelicko-augsburskiego w Polsce - Nowicka, Urszula (Ius Matrimoniale, 2015)
In times of multiculturalism and religious pluralism issue of mixed marriages it is very timely. It is an object of interest of all faiths and religions. The author of the present article takes the issue of mixed marriages from the point of view of three Christian faiths: Roman Catholic Church, the Orthodox Church and the Evangelical Church of the Augsburg Confession in Poland. Each of these churches makes his faithful requirements that are necessary to be able to to marry with a person of another faith or religion. Unfortunately, the similarity these norms can lead to difficulties in marriages of different religious or church affiliation.